Penelitian pemanfaatan kulit itik - Untari, Sri (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
Study on utilization of duck skins was intended to identify the right method of obtaining duck skins which could be utilized as maximum as possible, and it was conducted among others by observing the method of depilating feathers and obtaining quality duck skins. 24 duck of confine and tended were used in this study, and ther were 3 treat ments provided on the duck skins i.e : feasher depilation, no feather depilation and depilation using ash. The results of the study showed that the re were no significant between tended and confine duck skins (Pâ¤Â 0,05) on-the test results of tensile strength. On visual inspection of no depilated duck skins showed there was only 1 % damage occurred, but the feather coul be not be utilized, while 5% damage occurred on the depilated duck skins, but the feather could be not be utilized. It was suggested that the feather of the duck skins should be depilated before processing. Â INTISARI Â Yang dimaksud dengan Penelitian Pemanfaatan Kulit Itik ini ialah penelitian untuk mendapatkan kulit itik yang dapat dimanfaatkan semaksimal mungkin antara lain dengan penelitian cara pencabutan bulu yang baik. Penelitian ini menggunakan sampel 24 ekor itik yang terdiri dari itik terkurang dan itik gembala dengan 3 perlakuan yaitu : dicabut bulunya tanpa dicabut bulu dan dicabut bulu dengan abu gosok sebagai bahan pembantu. Hasil penelitian menunjukkan bahwa tidak ada bedaÂ nyata antara cara pencabutan bulu (P â¤ 0,05) pada hasil uji kekuatan tarik. Pada uji organoleptis kulit yang dicabut bulunya sebelum diproses kerusakan kulitnya 5% dan bulunya dapat dimanfaatkan. Disarankan agar dalam pemanfaatan kulit itik sebaiknya dilakukan pencabutan bulu sebelum diproses.Â